Examination of the fungal community on salt used in Turkish leather industry - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2005)
Tuz Lake and its salterns Kaldirim and Kayacik are major sources of solar salt for the Turkish hide industry. The fungal community on the salt, which may have detrimental effects if unprocessed salt is used in industrial processes such as in the leather industry, has not been previously investigated. Ten salt crystal and five brine samples were collected from Tuz Lake and its salterns for investigation. A total of 18 species belonging to 10 genera were encountered. Absidia, Acremonium, Eurotium, Aspergillus, Alternaria, Cladosporium, Eupenicillium, Penicillium, Stachybotrys, Trichoderma and Ulocladium species were isolated and identified. The results showed that Tuz Lake and its salterns contained diverse fungal communities. In conclusion the salt should not be used for the preservation of hide without purification because of the fungal contamination.
Keywords: EGYPTIAN SOILS; QUALITY; MARSHES; STRAINS; MOLD